eCPR Combined With Therapeutic Hypothermia Could Improve Survival and Neurologic Outcomes for Patients With Cardiac Arrest: A Meta-Analysis - Duan, Jingwei; Ma, Qingbian; Zhu, Changju; Shi, Yuanchao; Duan, Baomin (Frontiers in Cardiovascular Medicine, 2021)
Background: Extracorporeal membrane oxygenation with CPR (eCPR) or therapeutic hypothermia (TH) seem to be a very effective CPR strategy to save patients with cardiac arrest (CA). Furthermore, the subsequent post-CA neurologic outcomes have become the focus. Therefore, there is an urgent need to find a way to improve survival and neurologic outcomes for CA. Objective: We conducted this meta-analysis to find a more suitable CPR strategy for patients with CA. Method: We searched four online databases (Pubmed, Embase, CENTRAL and Web of science). From initial 1436 articles, 23 studies were eligible into this meta-analysis, including a total of 2035 patients. Results: eCPR combined with TH significantly improve the short-term (at discharge or 28 days) survival (OR = 2.27, 95% CIs [1.60–3.23], p < 0.00001) and neurologic outcomes (OR = 2.60, 95% CIs [1.92–3.52], p < 0.00001). At three months follow-up, the results of survival (OR = 3.36, 95% CIs [1.65–6.85], p < 0.0008) and favorable neurologic outcomes (OR = 3.02, 95% CIs [1.38–6.63], p < 0.006) were same as above. Furthermore, there was no difference in any bleeding needed intervention (OR = 1.33, 95% CIs [0.09–1.96], p = 0.16) between two groups. Conclusions: From this meta-analysis, we found that eCPR combining with TH might be a more suitable CPR strategy for patients with CA in improving survival and neurologic outcomes. And eCPR with TH did not increase the risk of bleeding. Furthermore, single-arm meta-analyses showed a plausible way of temperature and occasion of TH.